The movement of contemporary artworks in West Africa : case of art through the exemple of Senegal - (:unkn) unknown (My University, 2014)
The part of Africa in the world trade of cultural products and services remains very weak. This situation reflects partially the level of the exchanges involving this sector inside the continent. Growing constraints bear down on the flow of the artistic works but also on the conditions of their production. The works of contemporary art are not departed from this assertion. More and more publications and researches deal with the problem of the exchanges which underlies the flow of the works of contemporary art in Africa. It’s established nowadays that studying the phenomena and demonstrations of the circulation of the artistic products and particularity of the works of contemporary art is a complex matter. Because of the mixture of genders and origins inside the traditional and the contemporary art in Africa. Many problems connected to the contemporary art in Africa continue to be analyzed under the frame of the traditional art. This academic work is a contribution for the thought on the artistic creation; it aims to highlight the motives and modalities of the exchanges on the contemporary in western Africa. This PhD determines the existing relations between the field of creation and that of the reception in a perspective of development of the exchange on the works of contemporary art as well as its incidences on the creativity. We’ll demonstrate also that the flow of artistic products, assumed as intrinsic value of the evolution of the contemporary works and generally known fame of the artists, is supposed to compete more explicitly and, more effectively, to the development of the field of reception by contributing to the attractiveness of the market of the art. The lightings and the stimulations that this academic work could bring on the art’s market as well as the dispatching of the products of contemporary art in Senegal, will allow us to have a better approach on this question in the other countries of the sub- Saharan area.
Keywords: African Research